Analisis Pengendalian Kualitas Menggunakan Metode Statistical Quality Control (SQC) pada Produk DR 58 di PT Surya Gemilang Engineering - Kanaya Belinda Audina; Rizki Achmad Darajatun (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Every manufacturing company must maintain product quality to meet established standards. PT Surya Gemilang Engineering is a company that manufactures various machine components, of which one is DR 58 product. While the production is ongoing, several defects were found that affected the product’s quality. This study is conducted to examine the quality control of DR 58 by applying Statistical Quality Control (SQC). There are nine types of defects identified, namely: under flange thickness, over flange thickness, scratches, not machined, through holes, blind holes, excessive groove depth, oversized dimensions, and undersized dimensions. The analytical tools used The tools applied consist of the Control Chart, Cause-and-Effect Diagram, Scatter Diagram, Histogram, Check Sheet, and Pareto Diagram. The findings reveal that the main sources of defects come from environmental, method, machine, human, and material factors. The recommended improvements include regular operator training, scheduled machine maintenance, adjustment of work methods, proper material selection, and better workplace environmental conditions. The application of SQC methods helps the company objectively identify defect sources and formulate appropriate corrective actions, thus improving the quality of DR 58 products in a sustainable manner. Keywords: Defect Product, Quality Control, Statistical Quality Control